Role of tranexamic acid as an adjunctive for chronic sub dural hematoma for early resolution and reduced recurrence rate: a prospective case-control study - V., Sri Priyadharsan; Sankar, L. (International Surgery Journal, 2024)
Background: Literature shows the effective use of tranexamic acid to reduce CSDH either as a primary treatment or as an adjunctive treatment. However, literature lacks conclusive evidence on the use of tranexamic acid for CSDH. There are not many Indian studies also on this subject. This study was aimed at finding the effectiveness of tranexamic acid in reducing the recurrence rate following surgery and early resolution. Methods: From May 2023 to May 2024, single centric case control study was done in a tertiary care center (Government Mohan Kumaramangalam medical college hospital, Salem) in Southern India. All patients with chronic subdural hematoma with Markwalder grading 2-4 and grade 1 with midline shift more than 1 cm were included in the study. Patients with severe cardio-cerebrovascular disease, patients with allergy to tranexamic acid and patients not willing to participate were excluded from the study. Tranexamic acid was given at a dose of 500 mg twice a day for 10 days. Patients were allocated into two groups: group A: where tranexamic acid was used, group B: where tranexamic acid was not used. Results: The mean duration of hospital stay was lesser in tranexamic acid group (p<0.005). The mean SDH thickness was lesser at 4th and 8th week in tranexamic acid group (p<0.005). Recurrence rate was lesser in tranexamic acid group at three months (p>0.05). Conclusions: This study of patients with CSDH showed that the adjunctive use of TXA after burr-hole drainage is effective in achieving resolution of CSDH through faster hematoma reduction. TXA may have a favorable effect in reducing recurrence and can be administered safely in selected patients.